2018
DOI: 10.1136/heartjnl-2017-312255
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of ideal cardiovascular health in Peru

Abstract: BackgroundThe prevalence of and factors associated with ideal cardiovascular health (ICH) by sociodemographic characteristics in Peru is not well known.MethodsThe American Heart Association’s ICH score comprised 3 ideal health factors (blood pressure, untreated total cholesterol and glucose) and 4 ideal health behaviours (smoking, body mass index, high physical activity and fruit and vegetable consumption). ICH was having 5 to 7 of the ideal health metrics. Baseline data from the Center of Excellence in Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
48
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 30 publications
5
48
3
2
Order By: Relevance
“…Consistent with previous studies, cardiovascular health was significantly associated with lower age groups7 and female gender,7 31 each having higher proportion of ideal cardiovascular metrics in our study. Similarly, we found people with Janajati and Dalit ethnicities had lower ideal cardiovascular health, which also corresponds with a previous study where ethnic minority groups have been reported to have lower cardiovascular health due to adoption of Western diet, heavy drinking habits and sedentary lifestyle 32.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, cardiovascular health was significantly associated with lower age groups7 and female gender,7 31 each having higher proportion of ideal cardiovascular metrics in our study. Similarly, we found people with Janajati and Dalit ethnicities had lower ideal cardiovascular health, which also corresponds with a previous study where ethnic minority groups have been reported to have lower cardiovascular health due to adoption of Western diet, heavy drinking habits and sedentary lifestyle 32.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of achieving ICH results (5-7 ideal metrics) in the researched Polish population was higher than in the Iranian population [18], in the adult population of Republic of Serbia, as well as the adult population of Bosnia and Herzegovina [10]. However, their results were lower than the results of those from Brazil [19], the Canadian research conducted by Maclagan et al [20], the research of the population of Peru [17], and samples of the American population [21,22]. This study proves that the percentage of people with ICH living in rural areas was significantly lower than in those living in the urban areas (5.0% vs. 6.3%).…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of occurrence of all seven CVH indicators is low all over the world, and varies from 0.2% to 15%, depending on geographical location, age, gender, ethnic background, and education level [9,[14][15][16][17]. The rate of achieving ICH results (5-7 ideal metrics) in the researched Polish population was higher than in the Iranian population [18], in the adult population of Republic of Serbia, as well as the adult population of Bosnia and Herzegovina [10].…”
Section: Discussionmentioning
confidence: 99%
“…In an article featured in Heart , Benziger et al 5 describe the distribution of CVH in 3058 adults (mean age 55 years (SD 12), 51% women) from four different settings in Peru: the highly urbanised capital city, Lima; urban and rural Puno (high altitude, located on the shore of Lake Titicaca) and Tumbes (coastal semirural). The subjects are participants of the CRONICAS cohort study, which aims to investigate the impact of geographic variation, and thus urbanisation and environmental risk factors, in the progression of non-communicable diseases in Peru.…”
mentioning
confidence: 99%